INOVASI APLIKASI MOBILE BERBASIS KECERDASAN BUATAN PADA LAYANAN DINAS SOSIAL PROVINSI JAWA TIMUR MENGGUNAKAN METODE RAPID APPLICATION DEVELOPMENT - Kandhi Surya Atmadja (CV. Adiba Aisha Amira, 2026)
Delivering public services and social aid frequently faces hurdles regarding data precision and information access. This research focuses on the creation of a React Native-based mobile app prototype equipped with an AI chatbot, functioning as a digital information hub for the East Java Provincial Social Services. The study utilizes the Rapid Application Development (RAD) methodology, encompassing Requirements Planning, User Design (UI/UX with Figma), Construction (frontend with React Native, backend via Supabase, and AI training), and Cutover phases. This rapid iterative process produces the E-JSC application, a versatile platform featuring an AI chatbot (